Properties of SCC prepared using natural pozzolana and industrial wastes as mineral fillers. (September 2015) - Adekunle, Saheed; Ahmad, Shamsad; Maslehuddin, Mohammed; Al-Gahtani, Husain Jubran
Abstract: The high unit cost of self-consolidating concrete (SCC) resulting from the use of conventional filler materials, such as fly ash or silica fume, has been identified as the main hindrance to its widespread use particularly at places where these materials are not available locally. To achieve economy in the production of SCC, it is highly desirable to explore possibility of using alternative materials as mineral fillers through the evaluation of technical and economic benefits of SCC made with these materials. This paper presents the results of a study conducted to evaluate the performance of ternary SCC mixtures prepared using some industrial wastes as mineral fillers which include limestone powder, cement kiln dust, bag house dust, pulverized steel slag and metakaolin, each in conjunction with natural pozzolana. The mechanical properties and durability characteristics of the SCC mixtures satisfying the requirements of self-compactability at optimally selected dosages of chemical admixtures were evaluated. Except the SCC mixture incorporating bag house dust, the early and later-age strengths of the other SCC mixtures were found to be very high. Further, the good corrosion resistance exhibited by the developed SCC mixtures showed that the high performance SCC mixtures can be prepared utilizing these industrial wastes as mineral fillers.